Influence of maternal vaccination against diphtheria, tetanus, and pertussis on the avidity of infant antibody responses to a pertussis containing vaccine in Belgium. Issue 7 (3rd October 2017) - Caboré, Raïssa Nadège; Maertens, Kirsten; Dobly, Alexandre; Leuridan, Elke; Van Damme, Pierre; Huygen, Kris
ABSTRACT: Maternal antibodies induced by vaccination during pregnancy cross the placental barrier and can close the susceptibility gap to pertussis in young infants up to the start of primary immunization. As not only the quantity but also the quality of circulating antibodies is important for protection, we assessed whether maternal immunization affects the avidity of infant vaccine-induced IgG antibodies, in the frame of a prospective clinical trial on pregnancy vaccination in Belgium. Infants born from Tdap (Boostrix®) vaccinated (N = 55) and unvaccinated (N = 26) mothers were immunized with a hexavalent pertussis containing vaccine (Infanrix Hexa®) at 8, 12 and 16 weeks, followed by a fourth dose at 15 months of age. Right before and one month after this fourth vaccine dose, the avidity of IgG antibodies against diphtheria toxin (DT), tetanus toxin (TT), pertussis toxin (PT), filamentous hemagglutinin (FHA) and pertactin (Prn) was determined using 1.5 M ammonium thiocyanate as dissociating agent. In both groups, antibody avidity was moderate for TT, PT, FHA and Prn and low for DT after priming. After a fourth dose, antibody avidity increased significantly to high avidity for TT and PT, whereas it remained moderate for FHA and Prn and low for DT. The avidity correlated positively with antibody level in both study groups, yet not significantly for PT. When comparing both study groups, only PT-specific antibodies showed significantly lower avidity in infants born from vaccinated than from unvaccinated mothers after the fourth vaccine dose. The clinical significance of lower avidity of vaccine induced infant antibodies after maternal vaccination, if any, needs further investigation.